Role of the brain in the regulation process of urination - V. B. Berdichevskiy; A. A. Sufianov; V. G. Yelishev; D. A. Barashin (Андрология и генитальная хирургия, 2014)
The analysis of positron emission tomography of the brain with glucose isotope 18F-fluorodeoxyglucose in healthy men and women during the period of accumulation and emptying of the bladder revealed no gender-specific brain activity. The men and women during the accumulation and storage of urine occurs at a standard activity of the brain with the dominance of the left hemisphere. Zone hyperactivity of the brain during this period is the region of the back of the cingulate gyrus.During urination in both men and women have the increased activity of the cortex of the brain. Preserved the dominance of the left hemisphere. Hyperactivity zone of the brain during this period is the region of the anterior cingulate gyrus.Thus, the cortical control of the act of accumulation and bladder emptying in healthy people in our studies did not reveal gender differences. However, security features neurohumoral response of spinal centers and peripheral neuroregulation function of the lower urinary tract, may have a man and a woman significant differences.